WATERSHED MANAGEMENT APPROACH AS AN ALTERNATIVE SOLUTION FOR FLOOD PROBLEM IN NORTHERN PART OF CENTRAL JAVA (Pendekatan Pengelolaan DAS Sebagai Alternatif Solusi Masalah Banjir di Jawa Tengah Utara) - Endang Savitri; Rahardyan Nugroho Adi; Pamungkas Buana Putra; Yonky Indrajaya, S.Hut. MT (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2022)
ABSTRACTThe flood disaster in northern Central Java was caused by rainfall, the influence of tidal surges, and ground subsidence in various sites. This study aims to give alternative solutions to flood control in Central Java watersheds draining to the north coast. By identifying the flood water discharge areas, the amount of runoff causing flooding can be reduced. By overlaying maps of floodwater discharge, land cover, degraded land, and forest functions, 12 recomendations  of forests and land rehabilitation (RHL) are obtained, suited to the area's concerns. The recommendations are planned only for the areas with vulnerable and highly vulnerable to floodwater discharge, so priority is given to activities that incorporate runoff into the ground as much as possible to reduce the flood volume. The RHL is grouped into the enrichment of plants in open areas with the function of forest areas, enhancing terraces to reduce erosion, increasing soil fertility, and constructing infiltration wells or bio pores. Of the 31 regencies/cities whose rivers flow into the north coast, there are 5 (five) regencies/cities whose RHL recommendations are applied to more than 50% of the area, namely Salatiga City (99%), Semarang district/city (76%), Jepara Regency (71%), Pekalongan Regency (55%), and Brebes Regency (51%) .Keywords: Flood vulnerability, land rehabilitation activities, flood disasterABSTRAKBencana banjir di Jawa Tengah bagian utara disebabkan oleh curah hujan, pengaruh gelombang pasang, dan penurunan muka tanah di berbagai lokasi. Penelitian ini bertujuan untuk memberikan alternatif solusi pengendalian banjir di DAS Jawa Tengah yang bermuara di pantai utara. Dengan mengidentifikasi daerah debit air banjir, jumlah limpasan yang menyebabkan banjir dapat dikurangi. Dengan overlay peta debit air banjir, tutupan lahan, lahan terdegradasi, dan fungsi hutan, diperoleh 12 rekomendasi rehabilitasi hutan dan lahan (RHL) yang sesuai dengan kepentingan kawasan. Rekomendasi RHL hanya direncanakan untuk daerah yang rawan dan sangat rentan terhadap debit air banjir, sehingga prioritas diberikan pada kegiatan yang sedapat mungkin memasukkan limpasan ke dalam tanah untuk mengurangi volume banjir. RHL dikelompokkan menjadi pengayaan tanaman di areal terbuka dengan fungsi kawasan hutan, peninggian terasering untuk mengurangi erosi, peningkatan kesuburan tanah, dan pembuatan sumur resapan atau biopori. Dari 31 kabupaten/kota yang sungainya bermuara di pantai utara, terdapat 5 (lima) kabupaten/kota yang rekomendasi RHL diterapkan lebih dari 50% wilayahnya, yaitu Kota Salatiga (99%), Kabupaten/Kota Semarang (76%),  Kabupaten Jepara (71%), Kabupaten Pekalongan(55%), Kabupaten Brebes (51%).Kata kunci: Kerentanan banjir, kegiatan rehabilitasi lahan, bencana banjir